Comparison of the clinical effectiveness of different off‐loading devices for the treatment of neuropathic foot ulcers in patients with diabetes: a systematic review and meta‐analysis. Issue 3 (11th March 2013) - Morona, Judy K.; Buckley, Elizabeth S.; Jones, Sara; Reddin, Edith A.; Merlin, Tracy L.
Summary Effective off‐loading is considered to be an important part of the successful clinical management of diabetic foot ulcers. The aim of this systematic review is to investigate the safety and effectiveness of different off‐loading devices for the treatment of diabetic foot ulcers. The medical literature was extensively searched from January 1966 to May 2012. Systematic reviews and controlled studies that compared the use of different off‐loading devices formed the evidence base. Studies were critically appraised to determine their risk of methodological bias, and data were extracted. Results were pooled using random effects meta‐analysis and tested for heterogeneity. When compared with removable devices, non‐removable off‐loading devices were found, on average, to be more effective at promoting the healing of diabetic foot ulcers (RRp = 1.43; 95% CI 1.11, 1.84; I2 = 66.9%; p = 0.001; k = 10). Analysis, stratified by type of removable device, did not detect a statistically significant difference between non‐removable off‐loading devices and removable cast walkers; however, on average non‐removable off‐loading devices performed better than therapeutic shoes at promoting the healing of diabetic foot ulcers (RRp = 1.68; 95% CI 1.09, 2.58; I2 = 71.5%; p = 0.004; k = 6). The two types of non‐removable off‐loading devices i.e. total contact casts and instant total contact casts (removable cast walker rendered irremovable by securing with bandage or lace), were found to be equally effective (RRp = 1.06; 95% CI 0.88, 1.27; I2 = 3.3%; p = 0.31; k = 2). In conclusion, non‐removable off‐loading devices regardless of type, are more likely to result in ulcer healing than removable off‐loading devices, presumably because patient compliance with off‐loading is facilitated. Copyright © 2013 John Wiley & Sons, Ltd.